Voice disorders in teachers and occupational nursing care. - Cezar-Vaz, Marta Regina; Severo, Luana de Oliveira; Borges, Anelise Miritz; Bonow, Clarice Alves; Rocha, Laurelize Pereira; de Almeida, Marlise Capa Verde (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> Objective. To identify the occupational characteristics and their implications for the occurrence of voice disorders among teachers in early childhood and primary education. Methodology. A quantitative and exploratory research was undertaken in a metropolitan city of the state capital of Rio Grande do Sul/Brazil. The sample consisted of 37 teachers from early childhood and primary education. Results. All participants were female, with a mean age of 40 years. Seventy-eight percent indicated one or more voice disorders (54% hoarseness, 41% voice cracks, 27% voice loss and 3% coughing). The noisy school environment was identified as a possible triggering factor of the voice disorder in 49% of cases. Forty-six percent of all teachers indicated not doing any treatment in case of voice disorders. The most frequently used specific measures were: medication use (32%) and speech therapy (5%). Conclusion. Voice disorders are frequent among the participating teachers and are mainly related to a noisy school environment. It is important for the nurse to intervene, using educative strategies to reduce the risk factors for the vocal health of teachers working in these conditions. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->